Unusual {⋯HNC2O⋯HCnO}, n = 1 or 2, synthons predominate in the molecular packing of one-dimensional coordination polymers, {Cd[S2P(OR)2]2(3LH2)}n, for R = Me and Et, but are precluded when R = i-Pr; 3LH2 = N,N′-bis(3-pyridylmethyl)oxalamide - Tan, Yee Seng*; Yeo, Chien Ing*; Kwong, Huey Chong*; Tiekink, Edward R. T.* (Royal Society of Chemistry, 2022)
Linear, one-dimensional coordination polymers, {Cd[S2P(OR)2]2(3LH2)}n, for R = Me (1), Et(2) and i-Pr(3) have been fully characterised by a variety of physiochemical, spectroscopic, crystallographic and computational techniques. Two-dimensional layers are apparent in the crystals of 1 and 2, being mediated, respectively, by unusual {···HNC2O···HCnO}, n = 1 or 2, synthons formed between the oxalamide and phosphorus-bound alkoxy residues. Related synthons are not observed in the crystal of 3, with supramolecular tapes, mediated by concatenated {···HNC2O}2 synthons, being formed instead. The observed differences in supramolecular association are ascribed to the increased steric bulk and reduced inductive effect of the R = i-Pr group compared with R = Me and Et.